2010
DOI: 10.1016/j.jvs.2009.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion is associated with increased morbidity and mortality after lower extremity revascularization

Abstract: In a large number of patients undergoing lower extremity revascularization, we have found that there is a higher risk of postoperative mortality, pulmonary, and infectious complications after receiving intraoperative blood transfusion. Additional studies are necessary to better define transfusion triggers that balance the risk/benefit ratio for blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 35 publications
1
49
1
3
Order By: Relevance
“…anesthetized anemic sheep where transfusion of renitrosylated RBCs, but not untreated blood, increased kidney blood flow and maintained GFR. Intraoperative blood transfusion is a well-recognized risk factor for acute kidney injury (AKI) (43)(44)(45), and the incidence of transfusion-associated AKI is amplified by preoperative anemia (44). Thus, occurrence rates of AKI may be a useful measure of the O 2 delivery capability of banked blood.…”
Section: Discussionmentioning
confidence: 99%
“…anesthetized anemic sheep where transfusion of renitrosylated RBCs, but not untreated blood, increased kidney blood flow and maintained GFR. Intraoperative blood transfusion is a well-recognized risk factor for acute kidney injury (AKI) (43)(44)(45), and the incidence of transfusion-associated AKI is amplified by preoperative anemia (44). Thus, occurrence rates of AKI may be a useful measure of the O 2 delivery capability of banked blood.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In a study based on National Surgical Quality Improvement Program (NSQIP) report, dialysis requiring AKI after revascularization occurred in 0.5% of patients, and 30-day mortality was 2.7%. 19 There is no data available on the prevalence of less severe stages of AKI (non-dialysis requiring).…”
Section: Discussionmentioning
confidence: 99%
“…This is considered as an independent risk factor that increases peri-operative adverse outcomes [5,7]. Many studies demonstrated that there was an increased risk of postoperative mortality and morbidity including pulmonary and infectious complications after receiving intraoperative blood transfusions [8][9][10]. Thus, there has been an increased emphasis on the correction of preoperative anaemia to improve the patient's outcome and decrease the need for allogeneic blood transfusion.…”
Section: Design Overviewmentioning
confidence: 99%